Association between breastfeeding and risk of endometrial cancer: a meta-analysis of epidemiological studies. Issue 2 (March 2018) - Ma, Xiao; Zhao, Long-Gang; Sun, Jiang-Wei; Yang, Yang; Zheng, Jia-Li; Gao, Jing; Xiang, Yong-Bing
Abstract : Epidemiological studies have yielded inconsistent findings on the relationship between breastfeeding and the risk of endometrial cancer. Pertinent studies were identified by searching PubMed, Embase, and Web of Knowledge through February 2015 and by reviewing the reference lists of retrieved articles. Study-specific estimates were pooled using a random-effects model. Dose–response analysis was carried out for every 6-month increase in the duration of breastfeeding in relation to the risk of endometrial cancer. Three prospective and 11 case–control studies were included in this meta-analysis. The pooled estimates for ever compared with never breastfeeding and the longest duration of breastfeeding compared with the shortest were 0.91 [95% confidence interval (CI): 0.75–1.09] and 0.76 (95% CI: 0.59–0.98). The risk of endometrial cancer decreased by 7% for every 6-month increase in the duration of breastfeeding (relative risk: 0.93; 95% CI: 0.88–0.97). This study provides evidence that ever breastfeeding, particularly a longer duration of breastfeeding, is associated with a lower risk of endometrial cancer. Abstract : Supplemental Digital Content is available in the text.